Functions of EpCAM in physiological processes and diseases (Review) - Huang, Li; Yang, Yanhong; Yang, Fei; Liu, Shaomin; Zhu, Ziqin; Lei, Zili; Guo, Jiao (International journal of molecular medicine, 2018)
EpCAM (epithelial cell adhesion molecule) is a type I transmembrane glycoprotein, which was originally identified as a tumor-associated antigen due to its high expression level in rapidly growing epithelial tumors. Germ line mutations of the human EpCAM gene have been indicated as the cause of congenital tufting enteropathy. Previous studies based on cell models have revealed that EpCAM contributes to various biological processes including cell adhesion, signaling, migration and proliferation. Due to the previous lack of genetic animal models, the in vivo functions of EpCAM remain largely unknown. However, EpCAM genetic animal models have recently been generated, and are useful for understanding the functions of EpCAM. The authors here briefly review the functions and mechanisms of EpCAM in physiological processes and different diseases.